Self-Talk as A Psychological Strategy for Enhancing Student Engagement in Physical Education: A Systematic Literature Review (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2025)
This study aimed to identify factors that influence student learning outcomes and motivation in Physical Education through a systematic literature review. This study identified 577 research articles from Scopus database and SAGE publications published from 2014 to 2024. The article selection process used PRISMA flow diagram. According to the screening and eligibility review, five papers met the analytic requirements. The results of analysis show that a motivating environment promotes a sense of competency and participation as well as persistence in goal orientation. It also shows that self-talk helps students manage anxiety and boosts confidence. In addition, the use of technology, such as video-based learning, improves student understanding leading to increased engagement in Physical Education. Studies also show that self-talk is helpful for learning Physical Education. It can be a mental strategy, a tool for controlling emotions, and a reflection tool. Self-talk can help with anxiety management, confidence building, skill evaluation enhancement, and physical activity performance. Positive self-talk, technology, and inspiring surroundings could assist Physical Education process to be more accessible and successful. Therefore, this study underlines that psychological tactics must be included into Physical Education programs in schools to improve the student physical, cognitive, and emotional involvement.